THE ROLE OF PROMOTING AND SUPPORTING PHYSICAL ACTIVITY OF ELDERLY PEOPLE - Czarnecki, D.; Skalski, D. W.; Tsyhanovska, N.; Kindzer, B.; Vynogradskyi, B.; Dyachuk, V. P. (Rehabilitation and Recreation, 2023)
The aging process of the body leads to changes in three main areas: biological, psychological and social. It is extremely important to pay attention to the necessity and ability to motivate these people to undertake activities. It is also necessary to emphasize the need for cooperation of the entire medical team with family members and carers in nursing homes as part of the program of prevention and physiotherapy of the elderly, and to take actions aimed at reintegrating this group into social life. It is unquestionably stated that there is a great need for physiotherapy of the elderly, but the most important and the most difficult is to make them aware and encourage them to take action to improve their physical, psychological and social fitness. Seniors who have already given up and resigned can be stimulated to act again. A stimulus for change can be contact with a nice, warm, soothing, relaxing touch with healing power. We live in a rapidly aging society and we should direct all professional activities and our development towards this group. An active lifestyle allows you to maintain physical fitness and mental activity - intellectual fitness. Systematic physical activity counteracts the decline in psychophysical fitness of the elderly, enabling them to undertake previously abandoned activities. Every activity in old age brings benefits, regardless of the type and form. Activity tailored to the needs and capabilities of the target group always has a positive effect on the work of the nervous, circulatory, muscular and respiratory systems. It improves general physical efficiency, respiratory efficiency, heart function, exercise tolerance, body immunity and is the main element of anti-trauma prevention. In addition to the physical and physiological aspect, it plays an important psychological role, significantly improving well-being, self-esteem, comfort, independence and thus the quality of life, self-esteem, usefulness, acceptance of age and appearance. Elderly people who have become convinced that being active and needed at their age is possible do not need further arguments to remain in this belief, they willingly take part in physical activities, lectures, cultural events, occupational therapy workshops. Most often they are students of the University of the Third Age and they are doing great, sometimes they are more ambitious and motivated to learn than students two decades younger than them. They take care of their appearance, appearance, attractiveness, they experience a second youth.